Flies from L.A., The Sequel: A further twelve new species of Megaselia (Diptera: Phoridae) from the BioSCAN Project in Los Angeles (California, USA) - Hartop, Emily A. (Biodivers Data J, 2016)
Abstract. BACKGROUND: Presented are continued results from the BioSCAN Project, an urban biodiversity study sampling primarily from private backyards in Los Angeles, California (USA). Presented are continued results from the BioSCAN Project, an urban biodiversity study sampling primarily from private backyards in Los Angeles, California (USA). NEW INFORMATION: Twelve new species of Megaselia (Diptera: Phoridae) are described: M. baileyae, M. friedrichae, M. gonzalezorum, M. joanneae, M. losangelensis, M. phyllissunae, M. pongsaiae, M. shatesae, M. stoakesi, M. studentorum, M. voluntariorum, M. wongae.